Changes in soil microbial community structure following amendment of biosolids for seven years. Issue 1 (1st January 2019) - Hu, Yecui; Pang, Shuang; Yang, Junjie; Zhao, Xiaoguang; Cao, Jirong
ABSTRACT: The environment-friendly disposal approaches for sewage sludge remain a challenge worldwide, and agricultural application of the treated sewage sludge, i.e. biosolids, as soil conditioner and nutrient source for plants, is still one of the most promising options for dealing with the waste. In this study, we compared the effects of long-term applications of biosolids and mineral fertilizer on soil microbial community using phospholipid fatty acid profiles in an agricultural field. The microbes predominant in the mineral fertilizer soil remained the most abundant in the biosolids-amended soil. Bacterial and fungal communities presented downtrends in both absolute and relative amounts; however, percentage of Gram-positive bacteria remained unchanged. Soil pH displayed significant negative correlations with microbial communities and explained 64%, 56% and 44% of the variances in microbial biomass, bacteria and fungi, respectively, while soil NO3 – -N was positively correlated with microbial biomass, bacteria and fungi (r 2  = 0.53, 0.51 and 0.54, respectively).